A New Medical Device Rigeneracons Allows to Obtain Viable Micro‐Grafts From Mechanical Disaggregation of Human Tissues. Issue 10 (October 2015) - Trovato, Letizia; Monti, Manuela; del Fante, Claudia; Cervio, Marila; Lampinen, Milla; Ambrosio, Lucia; Redi, Carlo Alberto; Perotti, Cesare; Kankuri, Esko; Ambrosio, Gennaro; Rodriguez Y. Baena, Ruggero; Pirozzi, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> Autologous graft is considered the gold standard of graft materials; however, this approach is still limited due to both small amount of tissue that can be collected and to reduced cell viability of cells that can be obtained. The aim of this preliminary study was to demonstrate the efficacy of an innovative medical device called Rigeneracons® (CE certified Class I) to provide autologous micro‐grafts immediately available to be used in the clinical practice. Moreover, Rigeneracons® is an instrument able to create micro‐grafts enriched of progenitors cells which maintain their regenerative and differentiation potential. We reported preliminary data about viability cell of samples derived from different kind of human tissues, such as periosteum, cardiac atrial appendage biopsy, and lateral rectus muscle of eyeball and disaggregated by Rigeneracons®. In all cases we observed that micro‐grafts obtained by Rigeneracons® displayed high cell viability. Furthermore, by cell characterization of periosteum samples, we also evidenced an high positivity to mesenchymal cell markers, suggesting an optimal regenerative potential. J. Cell. Physiol. 230: 2299–2303, 2015. © 2015 Wiley Periodicals, Inc.